2009
DOI: 10.1148/radiol.2521081554
|View full text |Cite
|
Sign up to set email alerts
|

Dose Reduction and Compliance with Pediatric CT Protocols Adapted to Patient Size, Clinical Indication, and Number of Prior Studies

Abstract: Substantial dose reduction and high compliance can be obtained with pediatric CT protocols tailored to clinical indications, patient weight, and number of prior studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
86
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(93 citation statements)
references
References 18 publications
2
86
0
4
Order By: Relevance
“…Despite this shortcoming, the use of subjective image quality scores is an accepted method and in widespread use in clinical radiology. 5,13 In addition, the good interobserver variability of our readers validates the approach used in the study.…”
Section: Limitationssupporting
confidence: 58%
“…Despite this shortcoming, the use of subjective image quality scores is an accepted method and in widespread use in clinical radiology. 5,13 In addition, the good interobserver variability of our readers validates the approach used in the study.…”
Section: Limitationssupporting
confidence: 58%
“…Therefore, an alternative, radiation-free imaging modality is still being sought, especially in applications that require a large number of follow-up scans. 18 Over the past decade, MRI technology has been discussed as an alternative to CT technology for implant planning. 9,19,20 To date, most conventional MRI sequences only offer optimal soft-tissue images and lack the ability to image bone/air interfaces in the head area.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Besides minimizing tube current, the reduction of the tube voltage is a potent option to reduce radiation dose. Such lowkilovolt protocols are used in cerebral perfusion CT in the evaluation of patients with stroke 16 and in pediatric CT. 17 In phantom 18 as well as in clinical studies, it has been demonstrated that this technique can also be used in chest and abdominal imaging in adults. [19][20][21][22][23][24] Lower tube voltage in CTA results in higher noise levels on one hand, but the attenuation of iodine is increased 25,26 on the other hand.…”
mentioning
confidence: 99%